A new voltage doubler based DC-DC 2LCm-Y power converter topologies for high-voltage/low- current renewable energy applications - Bhaskar, Mahajan Sagar; Padmanaban, Sanjeevikumar; Wheeler, Patrick; Blaabjerg, Frede; Siano, Pierluigi (2018)
In this treatise, a new voltage doubler based DCDC 2LCm-Y power converter topologies are uttered for the high voltage/low-current renewable energy applications. L-Y, 2L-Y, 2LC-Y and 2LCm-Y power converter categories are recently proposed in the existing X-Y converter family. To provide an effective and viable solution to renewable energy system; four new voltage doubler based converters (2LCm-LVD, 2LCm-2LVD, 2LCm-2LCVD and 2LCm-2LCmVD converters) are proposed in 2LCm-Y converter category. The proposed converters are well suited for renewable energy applications which required high output voltage power converter such as a Photovoltaic Multilevel DC-AC converter system, renewable High Voltage Direct Current (HVDC) applications, Hybrid Electric Vehicles (HEV) etc. The perceptible characteristics of proposed 2LCm-Y power converter topologies are presented in detail. Working of 2LCm-Y proposed converters with the derivation of VO/Vin is discussed in detail. Proposed converter topologies are simulated in the Numerical Computing Matrix Laboratory 9.0 (R2016a) software. The simulation results are discussed in details and it constantly showed the high- quality agreement with hypothetical analysis and validates the functionality and characteristics of the proposed 2LCm-Y converter topologies of X-Y converter family.